Is personal trust related to mistrust of university health care centre? - Abd Hamid, Harris Shah; Alwi, Azlin (2017)
Personal characteristics like gender have been shown to be related to people’s attitude towards medical treatment. A negative attitude towards health care provider can be expressed as mistrust. This paper examines the relationship between personal characteristics (personal trust, sex, and whether or not the person had obtained treatment at a health care centre) and mistrust to a university health care centre. Survey respondents are 420 university students with age ranging from 18 to 29 (M=21.6, SD=1.26). The finding reveals that personal trust is not related to mistrust towards healthcare provider. Both types of trusts were similar between the sexes and between students who had and had not visited the health care centre. Further studies are needed to establish the extent to which a domain-specific mistrust has marginal benefits over a generalised personal trust.